Bedside Ultrasound to Facilitate Early Diagnosis and Ease of Follow-Up in Neurogenic Heterotopic Ossification: A Pilot Study From the Intensive Care Unit. Issue 6 (November 2017) - Stefanidis, Konstantinos; Brindley, Peter; Ramnarine, Raymond; Blaivas, Michael; Daneshi, Mohammad; Sidhu, Paul S.; Alharthy, Abdoulrahman; Karakitsos, Dimitrios
Abstract : Objective: To explore the potential role of ultrasound (US) as a bedside tool in intensive care unit patients with presumed neurogenic heterotopic ossification (NHO). Setting: Tertiary university teaching hospitals. Participants: Critical care patients with acquired brain injury. Design: A multicenter prospective study of critical care patients with possible NHO. Main Measures: Following a screening clinical examination, the major joints were evaluated with US, serum laboratory work, and x-ray. Results: A total of 310 patients had decreased range of motion by clinical screen and all received US interrogation. Sonographic signs of NHO were identified in 21 of the 310 patients (6.8%), of which 17/21 (81.0%) showed hyperemia; 9/21 (42.8%) showed the reverse zone phenomenon, and 4/21 patients (19.0%) showed the prezone phenomenon. All 21 patients progressed to the zone phenomenon within 15 weeks. Laboratory parameters were not significantly correlated with US ( r = 0.11, r = 0.13; P > .05, respectively), whereas x-rays were associated with a mean diagnostic delay of 2 ± 0.5 weeks ( P < .05) compared with US. All 21 sonographic NHO patients survived to intensive care unit discharge. Twelve months after admission, 3/21 had died; 6/21 still had abnormalities by x-ray, US, and clinical examination; and 12/21 had resolution by x-ray, US, and clinical examination. Conclusion: Our pilot study suggests potential benefits for bedside US in NHO, especially when compared with x-ray or laboratory investigations. These include the possibility of earlier diagnosis, consideration of therapy before ossification, and ease of follow-up. Our study also provides insights into the morphologic, sonographic, radiologic, and clinical course of NHO.